Model-based estimation of land subsidence in Kathmandu Valley, Nepal - Shrestha, P.K.; Shakya, N.M.; Pandey, Vishnu Prasad; Birkinshaw, S.J.; Shrestha, S. (Informa UK Limited, 2017)
This study is the first to assess land subsidence in the Kathmandu Valley, Nepal. Land subsidence simulations were based on a fully calibrated groundwater (GW) flow model developed using a coupled surface–subsurface modelling system. Subsidence is predicted to occur as a result of deep aquifer compaction due to excessive GW abstraction. The north and north-east areas at the periphery of the GW basin are hotspots for this subsidence. The estimated subsidence is most sensitive to changes in land cover within the recharge areas. The model shows the Melamchi water supply project assists in the control of subsidence to some extent. In the absence of land subsidence measurements, this paper highlights the location and the potential levels of the subsidence hazard which will be useful for hazard prevention management. Additionally, this work provides a basis to design field investigations, monitoring networks for land subsidence and upgrading the present GW monitoring network. Although the study has presented a preliminary analysis, a more comprehensive model inclusive of clay subsidence is required to address the subsidence vulnerability of the central densely populated core of the valley, which reflects the need for a comprehensive database of the hydrogeology in the valley.